Cross country : fifteen years and ninety thousand miles on the roads and interstates of America with Lewis and Clark, a lot of bad motels, a moving van, Emily Post, Jack Kerouac, my wife, my mother-in law, two kids, and enough coffee to kill an elephant /: fifteen years and ninety thousand miles on the roads and interstates of America with Lewis and Clark, a lot of bad motels, a moving van, Emily Post, Jack Kerouac, my wife, my mother-in law, two kids, and enough coffee to kill an elephant. (2007) - Unknown
No abstract available